VARIASI PADAT TEBAR TERHADAP PERTUMBUHAN UDANG VANNAMEI (Litopenaeus vannamei) DENGAN PEMELIHARAAN PADA KOLAM TERPAL HIGH DENSITY POLYETHYLENE (HDPE) - Syahril, Alfis; Samuki, Khairul; Irhami, S; Hasibuan, M Barru Airil Fizra; Hendri, Afrizal; Isbah, Faliqul (Universitas Gajah Putih, 2024)
Vaname shrimp (Litopenaeus vannamei) is a type of shrimp that has high economic value and has great potential as an export commodity. The aim of the research was to analyze growth parameters, specific growth rate (SGR) and feed efficiency of vannamei shrimp in HDPE (High Density Polyethylene) tarpaulin ponds with different stocking densities. The research was carried out for 5 months with three treatments (stocking density of 100 shrimp/m3, dense stocking of 150 shrimp/m3 and dense stocking of 200 shrimp/m3) with 3 replications each. The results of the research on the specific growth rate (SGR) parameter had a significant effect (P>0.05), while the feed efficiency level (EP) parameter had no significant effect) on different densities in high Density Polyethylene (HDPE) tarpaulin ponds. The best specific growth rate (SGR) variable was in the 100 head/m2 stocking density treatment with a value of 9.72 ± 0.13b%, while the best feed efficiency variable in the 100 head/m2 treatment was 73.98 ± 5.09a%. Based on this, the treatment of 100 shrimp/m3 is the optimal dense stocking treatment.